2022
DOI: 10.3390/economies10120311
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Banks’ Stability in Jordan

Abstract: This paper aims to examine the determinants of financial stability in Jordanian commercial banks based on annual data for the period from 2011 to 2018. Based on the pooled effect model, this study shows that SME loans and capital adequacy positively and statistically affect the stability of Jordanian commercial banks, while financial inclusion, liquidity risk and credit risk negatively and statistically affect the stability of Jordanian commercial banks. The study recommends increasing the directing of bank lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Notably, the study found a significant performance disparity, with larger banks outperforming their smaller and medium-sized counterparts, establishing bank size as an important determinant of efficiency. Kharabsheh and Gharaibeh (2022) conducted a comprehensive investigation into the factors influencing financial stability within the context of Jordanian banks. The findings of their study revealed a significant and positive impact on the stability of commercial banks in Jordan attributable to SME loans and capital adequacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notably, the study found a significant performance disparity, with larger banks outperforming their smaller and medium-sized counterparts, establishing bank size as an important determinant of efficiency. Kharabsheh and Gharaibeh (2022) conducted a comprehensive investigation into the factors influencing financial stability within the context of Jordanian banks. The findings of their study revealed a significant and positive impact on the stability of commercial banks in Jordan attributable to SME loans and capital adequacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The investigation found that funding risk significantly enhances banks’ sustainability. In earlier work, Salike and Ao (2018), Chai et al (2022) and Kharabsheh and Gharaibeh (2022) looked at how various risk categories affected the stability of 15 Pakistani banks between 2009 and 2020. The empirical results show that while financing risk has no discernible impact on stability, both credit risk and liquidity risk are inversely correlated with the stability of banking sector.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…According to theory, FI and DFSs can minimize problems with agency and knowledge imbalances between lenders and borrowers (Beck et al , 2014; Agur et al , 2020; Kharabsheh and Gharaibeh, 2022). In addition, FI and DFSs can result in greater stability because it has the potential to draw funds from a broad client base, hence, lowering the volatility of bank financing.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations